Wordsworth's poetry of repetition romantic recapitulation - Houghton-Walker, Sarah (Oxford University Press, 2023)
This text explores those moments of repetition, placing them in the early nineteenth century context from which they emerged, and teasing out through extended close attention to the poetry itself the complexities of repetition and recapitulation.
Keywords: Wordsworth, William -- 1770-1850; Lyrik; Wiederholung -- Motiv; Wordsworth, William / 1770-1850 / Criticism and interpretation; Repetition in literature; Literature; Literature: history & criticism